2020
DOI: 10.3390/jof6010036
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Chest Computed Tomography as Standard of Care in High-Risk Hematology Patients

Abstract: Baseline chest computed tomography (BCT) in high-risk hematology patients allows for the early diagnosis of invasive pulmonary aspergillosis (IPA). The distribution of BCT implementation in hematology departments and impact on outcome is unknown. A web-based questionnaire was designed. International scientific bodies were invited. The estimated numbers of annually treated hematology patients, chest imaging timepoints and techniques, IPA rates, and follow-up imaging were assessed. In total, 142 physicians from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The early onset of IFD observed in our study is in keeping with recent adult data demonstrating high prevalence of IFD early in AML therapy, consistent with the inherent immunodeficiency associated with the AML disease process 33 . A role for baseline computerised tomography (CT) imaging for early detection of IFD in adult patients with de novo AML has been proposed 33 ; however, early imaging is not considered standard practice at present at adult centres 34 . Our findings of high prevalence of IFD in the period immediately following AML diagnosis suggest a broad systems based approach is required to identify patients at highest risk of IFD, implement prophylaxis from the start of treatment and facilitate timely diagnostic testing to minimise time to initiation of appropriate antifungal therapy.…”
Section: Discussionsupporting
confidence: 87%
“…The early onset of IFD observed in our study is in keeping with recent adult data demonstrating high prevalence of IFD early in AML therapy, consistent with the inherent immunodeficiency associated with the AML disease process 33 . A role for baseline computerised tomography (CT) imaging for early detection of IFD in adult patients with de novo AML has been proposed 33 ; however, early imaging is not considered standard practice at present at adult centres 34 . Our findings of high prevalence of IFD in the period immediately following AML diagnosis suggest a broad systems based approach is required to identify patients at highest risk of IFD, implement prophylaxis from the start of treatment and facilitate timely diagnostic testing to minimise time to initiation of appropriate antifungal therapy.…”
Section: Discussionsupporting
confidence: 87%
“…The median IPA incidence rate did not differ between centers that did baseline CT (9%) and those which did not (7%). 16 The incidence of pre-HCT chest CT abnormalities is to the tune of 13.6%-55% 6-11 (Table 2). Our study had a 38% incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup analysis of newly diagnosed HM (AML) patients, 10% (11 of 107) had IPA identified on baseline chest CT and positive Aspergillus galactomannan (GM) in bronchoalveolar lavage (BAL) fluid [ 11 , 12 ]. Most of these patients (8 of 11) were not neutropenic and (6 of 11) lacked symptoms [ 13 ]. Due to a lack of patient-level information, these 11 patients were not included in our review.…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of patient-level information, these 11 patients were not included in our review. In a web-based survey study, authors found a 9% IPA rate detected by baseline chest CT in high-risk HM patients compared with a 7% median IPA rate detected in high-risk HM patients at centers that did not use baseline chest CT [ 13 ]. Data for rates of IPA on baseline CT for newly diagnosed AML were not available.…”
Section: Discussionmentioning
confidence: 99%